EFFECT OF DIFFERENT NITROGEN, PHOSPHORUS AND POTASSIUM LEVELS ON SESAME (SESAMUM INDICUM) IN BASTAR PLATEAU OF CHHATTISGARH - ASHWANI KUMAR THAKUR; ADIKANT PRADHAN; RAKESH KUMAR PATEL; ADIKANT; PRAFULL KUMAR (The Bioscan, 2015)
The experiment was conducted under field conditions at SG College of Agriculture and Research Station, Jagdalpur during Kharif season 2012 and 2013. The experiment was laid out in Randomized Block design with factorial arrangement in three replications had three nitrogen levels (15, 30 and 45 kg ha-1), two phosphorus levels (30 and 60 kg ha-1)and three potassium levels(10, 20 and 30 kg ha-1). On the basis of two years experiment, nitrogen level 45 kg ha-1 recorded highest number of seeds pod-1(48.63 and 49.58) during 2012 and 2013. Phosphorus and potassium level shows no significant effect during both the years of experimentation. Seed yield and test weight was recorded significantly higher in nitrogen level 45 kg ha-1 (7.13 q ha-1, 7.81 q ha-1 and 3.57 g, 3.59 g) than the other levels. Application of 60 kg P2O 5 ha-1 recorded significantly highest seed yield (6.17 and 6.83 q ha-1) and test weight (3.20 g and 3.25g) during 2012 and. K30 kg ha-1 recorded significantly highest seed yield (6.111 and 6.71 q ha-1) during both the year during experimentation.